Las zonas neurogénicas en el adulto y su relación con las enfermedades neuropsiquiátricas. - Ramírez-Rodríguez, Gerardo; Carmen Silva-Lucero, María del; Gómez-Virgilio, Laura; del Ángel Ocaña-Femández, María; Ortiz-López, Leonardo; Torres-Pérez, Mario O.; Meraz-Ríos, Marco Antonio (Salud Mental)
Neuropsychiatry diseases (NPD) are characterized by changes in brain plasticity involving alterations in the morphology and functionality of neurons. However, affectations of the neuronal development (neurogenesis) in the adult brain are also shown. The neurogenic process is widely regulated by different factors such as genes, microenvironment, hormones, neurotransmitters, environmental cues and, also, nutrition. Thus, alterations in these factors negatively impact the neuronal development. Several studies performed in humans have revealed alterations of neurogenesis in NPD. However, most of the knowledge derives from studies done in animal models of NPD. The evidences from animal models are controversial, thus the use of human-induced pluripotent stem cells as a model of NPD has marked a way to study alterations in the neuronal development. Recently, the use of another cellular model for studying NPD has been proposed. Multipotent stem cells derived from olfactory epithelium (MOESCs) are a good candidate. However, evidences are scarce and deeper studies are necessary to know if there is or not a correlation of alterations in neuronal development in the OE with the changes observed in the brain; or if the MOESCs can mimic alterations shown in NPD that could let to get more knowledge about the factors promoting these diseases. Thus, in this review we discuss basic information about adult neurogenesis under physiological and non-physiological conditions in the hippocampus, olfactory bulb and olfactory epithelium.